Fostering Human Dignity Through Prayer - Kenney, Timothy (Lumen et Vita, 2015)
This paper examines the role of prayer, in the relationship between individuals and God, as expressive of human dignity. Humanity’s role within creation as ‘imago dei’ is most perfectly expressed and put into action through the prayer of the believer. The Incarnation is central to this claim, as through it Christ becomes the central model of life in the image and likeness of God for all humanity. In him one sees the life given over to continuous relationship with God, serving through his prayer at all times. Living out this relationship, which is most fully achieved through prayer, becomes a universal vocation, the goal of our lives, fulfilling our humanity and role within creation. In support of this view, this paper analyzes Hans Urs Von Balthasar’s Prayer. He roots his argument for pursuing prayer in the experience of the Son and presents it as the model through which we can be saved. Christ, through the Incarnation, becomes the recapitulator, the paradigmatic human who we are called to emulate and mirror. In our changing religious and political climate, there is a renewed need in the Church for Christians to pursue and live this vocation to prayer. Two scripture sources, 1 Thessalonians 5:17 and Luke 11:8-10, offer instruction on the way we can fulfill our human dignity with prayer. Read together, they reveal two paths: prayer as service and prayer as a persistent act. The goal of our lives on earth and our fulfillment as imago dei is found in prayer as contemplation, service, and an unceasing relationship with God.